2013
DOI: 10.2337/dc12-1020
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menopause, Reproductive Life Span, and Type 2 Diabetes Risk

Abstract: OBJECTIVEAge at menopause is an important determinant of future health outcomes, but little is known about its relationship with type 2 diabetes. We examined the associations of menopausal age and reproductive life span (menopausal age minus menarcheal age) with diabetes risk.RESEARCH DESIGN AND METHODSData were obtained from the InterAct study, a prospective case-cohort study nested within the European Prospective Investigation into Cancer and Nutrition. A total of 3,691 postmenopausal type 2 diabetic case su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
160
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(175 citation statements)
references
References 39 publications
7
160
1
7
Order By: Relevance
“…Cross-sectional studies examining the association between age at menopause and type 2 diabetes have yielded contradictory results, showing either no association or an increased prevalence of type 2 diabetes in women who experience early onset of menopause [5][6][7]. Similar to our findings, Brand and colleagues, in a nested case-cohort study, showed an increased risk of type 2 diabetes with early onset menopause, reporting similar size effects to those of the current investigation (HR 0.93 per 1 year older at menopause) [8]. However, we extended their findings and showed that this association was independent of potential mediators, including endogenous sex hormone levels.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Cross-sectional studies examining the association between age at menopause and type 2 diabetes have yielded contradictory results, showing either no association or an increased prevalence of type 2 diabetes in women who experience early onset of menopause [5][6][7]. Similar to our findings, Brand and colleagues, in a nested case-cohort study, showed an increased risk of type 2 diabetes with early onset menopause, reporting similar size effects to those of the current investigation (HR 0.93 per 1 year older at menopause) [8]. However, we extended their findings and showed that this association was independent of potential mediators, including endogenous sex hormone levels.…”
Section: Discussionsupporting
confidence: 75%
“…Data from cross-sectional studies examining the association between age at menopause and type 2 diabetes are contradictory, with a few studies reporting no association and some other reporting higher odds of having type 2 diabetes with early onset of menopause [5][6][7]. Recently, a nested case-cohort study reported that an increased risk of type 2 diabetes is associated with early onset of menopause, but it did not adjust for potential intermediate risk factors such as glucose metabolism, insulin or shared genetic factors [8]. Menopause transition is associated with weight gain, an increase in visceral fat and impairment of glucose homeostasis, all of which are important risk factors for type 2 diabetes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In that cohort of women with glucose intolerance, however, the low risk with oophorectomy was restricted to those women randomized to receive intensive lifestyle intervention but was An earlier age at natural menopause/ surgery and a shorter reproductive life span were also associated with diabetes in the NEFS. Previous studies regarding menopausal age are mixed, with some identifying no association after adjusting for confounders (36,37), while others observed a positive association (1,38 …”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus is common in postmenopausal women and is a major risk factor for cardiovascular disease, the leading cause of mortality in women in industrialized countries (1). In the United States, at least 1.8 million women of reproductive age years) are estimated to have diabetes, compared with 3.8 million among women aged 45-65 years (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation